Adoption of innovative e-learning support for teaching: A multiple case study at the University of Waikato - Johnson, E. Marcia; Cowie, Bronwen; De Lange, Willem; Falloon, Garry; Hight, Craig; Khoo, Elaine (Australasian Journal of Educational Technology, 2011)
In response to recent social, economic, and pedagogical challenges to tertiary-level teaching and learning, universities are increasingly investigating and adopting e-learning as a way to engage and motivate students. This paper reports on the first year of a two-year (2009-2010) qualitative multiple case study research project in New Zealand. Using perspectives from activity theory and the scholarship of teaching, the research has the overall goal of documenting, developing, and disseminating effective and innovative practice in which e-learning plays an important role in tertiary teaching. A "snapshot" of each of the four 2009 cases and focused findings within and across cases are provided. This is followed by an overall discussion of the context, "within" and "across" case themes, and implications of the research.